Short Communication: A small-scale coprological survey of the endoparasites in the Himalayan goral Naemorhedus goral (Hardwick, 1825) in Nepal - Jagan Nath Adhikari; Roshan Babu Adhikari; Bishnu Prasad Bhattarai; Tej Bahadur Thapa; Tirth Raj Ghimire (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Adhikari JN, Adhikari RB, Bhattarai BP, Thapa TB, Ghimire TR. 2021. Short Communication: A small-scale coprological survey of the endoparasites in the Himalayan goral Naemorhedus goral (Hardwick, 1825) in Nepal. Biodiversitas 22: 1285-1290. This study was carried out to detect the various endoparasites in the fecal samples of the Himalayan goral Naemorhedus goral (Hardwicke, 1825) from a forest patch of Rumsi area, the Seti River basin, Tanahun district, Nepal. Importantly, 17 fecal samples (89.5%) were positive for different parasites. Their positive rates showed the following orders as Strongyle (73.7%), Entamoeba sp. (52.6%), Strongyloides sp. (52.6%), Cryptosporidium sp. (26.3%), Cyclospora sp. (26.3%), Eimeria sp. (10.5%), Mullerius capillaris (10.5%), and Blastocystis sp. (5.3%). These results showed the prevalence status of the endoparasites in the Himalayan goral. This study provides general knowledge about the parasitic community using a non-invasive method. This is the first work in Himalayan goral of Nepal, hence intensive study to the other parts of Nepal is recommended.